Using species connectivity to achieve coordinated large-scale marine conservation efforts in the Red Sea. (May 2021) - Gajdzik, Laura; Green, Alison L.; Cochran, Jesse E.M.; Hardenstine, Royale S.; Tanabe, Lyndsey K.; Berumen, Michael L.
Abstract: In the face of increasing anthropogenic threats, coastal nations need to reach common ground for effective marine conservation. Understanding species' connectivity can reveal how nations share resources, demonstrating the need for cooperative protection efforts. Unfortunately, connectivity information is rarely integrated into the design of marine protected areas (MPAs). This is exemplified in the Red Sea where biodiversity is only nominally protected by a non-cohesive network of small-sized MPAs, most of which are barely implemented. Here, we showcase the potential of using connectivity patterns of flagship species to consolidate conservation efforts in the Red Sea. We argue that a large-scale MPA (LSMPA) would more effectively preserve Red Sea species' multinational migration routes. A connectivity-informed LSMPA approach provides thus one avenue to unite coastal nations toward acting for the common good of conservation and reverse the global decline in marine biodiversity. Highlights: The Red Sea is under increasing human threats but is not cohesively protected Paucity of connectivity information used to create existing marine protected areas Migration routes and aggregation sites of marine species connect multiple nations Transboundary connectivity patterns require coordinated, large-scale protection Connectivity can unite the Red Sea's nations toward concerted marine conservation efforts